Characterization of the surface acoustic wave devices based on ZnO/nanocrystalline diamond structures. Issue 8 (3rd April 2013) - Pang, Hua‐Feng; Garcia‐Gancedo, Luis; Fu, Yong Qing; Porro, Samuele; Gu, Yan‐Wei; Luo, J. K.; Zu, Xiao‐Tao; Placido, Frank; Wilson, John I. B.; Flewitt, Andrew J.; Milne, W. I.
Abstract Nanocrystalline ZnO films with strong (0002) texture and fine grains were deposited onto ultra‐nanocrystalline diamond (UNCD) layers on silicon using high target utilization sputtering technology. The unique characteristic of this sputtering technique allows room temperature growth of smooth ZnO films with a low roughness and low stress at high growth rates. Surface acoustic wave (SAW) devices were fabricated on ZnO/UNCD structure and exhibited good transmission signals with a low insertion loss and a strong side‐lobe suppression for the Rayleigh mode SAW. Based on the optimization of the layered structure of the SAW device, a good performance with a coupling coefficient of 5.2% has been realized, promising for improving the microfluidic efficiency in droplet transportation comparing with that of the ZnO/Si SAW device. An optimized temperature coefficient of frequency of −23.4 ppm °C−1 was obtained for the SAW devices with the 2.72 µm‐thick ZnO and 1.1 µm‐thick UNCD film. Significant thermal effect due to the acoustic heating has been redcued which is related to the temperature stability of the ZnO/UNCD SAW device.